THE ROLE AND EVOLUTION OF ENVIRONMENTAL POLICY IN THE HISTORY OF WORLD DIPLOMACY AND INTERNATIONAL RELATIONS AND ITS DEVELOPMENT IN UZBEKISTAN - Shakhnoza Saidova (Scholar Express Journal, 2025)
This article analyzes the role of historical science in the study of environmental policy processes in the context of world politics and diplomacy. International relations, which are increasingly forced to proceed from environmental realities, are a modern truth dictated by external climatic factors. The course of development of this type of transnational relations creates a new historical stage in world diplomacy
Keywords: environmental policy; climate policy; environmental diplomacy